(3GddHGH aj Ydhe GdcJGHs - (3YeQ Hf Ydj Hf YGOd GdMfHdj GdOeTbj, CHh MaU, SQGL GdOjf,J (B879 (3g` s
(3ChdgG (B:s
(3bhdg JYGdi (B(((3jSJHTQhf HfYeI ef Gddg haVd (B)) (3ddeG Hjf JYGdi Cfge jSJHTQhf HGdPjf de jdMbhG Hge Hjf gfG Cfge jSJHTQhf dCfaSge HeG QRbhG ef GdfYje s
(3BNQgG (B:s
(3Je GdLRA GdKGdK ef GddHGH ef Ydhe GdcJGH HMeO Gddg JYGdi jJdhg GdLRA GdQGHY Ef TGA Gddg JYGdi bhdg JYGdi (B(( (3hEP bGd EHQGgje dCHjg BRQ(B)) s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B58 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B300s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1543s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs